Section 3: Health Information Systems: Expanding the Scope of Health Information Systems - Kuhn, K. A.; Wurst, S. H. R.; Bott, O. J.; Giuse, D. A. (Yearbook of Medical Informatics, 2006)
To identify current challenges and developments in health information systems.Reports on HIS, eHealth and process support were analyzed, core problems and challenges were identified.Health information systems are extending their scope towards regional networks and health IT infrastructures. Integration, interoperability and interaction design are still today’s core problems. Additional problems arise through the integration of genetic information into the health care process. There are noticeable trends towards solutions for these problems.
Keywords: Health Information System; Information System; eHealth